Body Language and Gestures of Teachers in Virtual Meeting during Online Physical Education Learning in Elementary School - Wicahyani, Sri; Williyanto, Septian; Pardiman, Pardiman; Saputra, Deddy Rahmat (Universitas Pendidikan Indonesia, 2021)
The purpose of this study was to analyze the importance of teacher body language and gestures in virtual meetings during online Physical Education learning in Elementary School. This research is qualitative descriptive research conducting a literature study. The steps taken were article compilation, data reduction, data analysis, data presentation, and drawing conclusions. The researchers made an instrument for article determination criteria based on the PICOT criteria (Population, Intervention, Comparison, Outcome, and Time). The results of the study show that online learning, where the learning process could be carried out through video conferencing, could not only enable participants to interact through audio but also through an indirect face-to-face meeting. Nonverbal communication, including facial expressions and gestures, provided clear information from the speaker. Facial expressions, eye contact, physical appearance, and other aspects help the speaker express messages or information clearly. Facial expressions were more effective than other non-verbal cue modes. This research concludes that the online Physical Education learning in Elementary School implemented through virtual meeting media requires body language and gestures. The teacher should use special tricks in delivering practical learning materials delivered through virtual meetings.